2012
DOI: 10.1080/10962247.2012.742027
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 mass and species trends in Santiago, Chile, 1998 to 2010: The impact of fuel-related interventions and fuel sales

Abstract: Improving air quality in Santiago has been a high priority for the Chilean government. In this paper, we examine trends of fine particulate matter (PM 2.5 ) mass and species concentrations during the period 1998 to 2010 and explore the impact of fuel-related interventions and fuel sales on concentration changes. Smoothing spline functions were utilized to characterize and account for nonlinear relationships between pollutant concentrations and different parameters. Meteorology-adjusted PM 2.5 concentrations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 25 publications
4
21
0
Order By: Relevance
“…There were 2 to 5 air pollution episodes each month (at least two consecutive days when the Beijing average concentration exceeded 75 µg·m −3 ). PM 2.5 levels tended to be lowest in summer (particularly in August), and highest in winter, a pattern frequently observed elsewhere (Dimitriou and Kassomenos, 2014; Jhun et al, 2013; M.Marcazzan et al, 2001; Yang, 2002). Winters in Beijing are associated with conditions that prevailed in the “classical” air pollution episodes of the earthly and mid-20 th century, namely, high emissions of particulate and gaseous pollutants from coal consumption for heating and industry, and frequent stagnation conditions due to subsidence inversions that impede pollutant dilution and transport (Hu et al, 2013; Shi et al, 2003; Zhao et al, 2009).…”
Section: Resultssupporting
confidence: 68%
“…There were 2 to 5 air pollution episodes each month (at least two consecutive days when the Beijing average concentration exceeded 75 µg·m −3 ). PM 2.5 levels tended to be lowest in summer (particularly in August), and highest in winter, a pattern frequently observed elsewhere (Dimitriou and Kassomenos, 2014; Jhun et al, 2013; M.Marcazzan et al, 2001; Yang, 2002). Winters in Beijing are associated with conditions that prevailed in the “classical” air pollution episodes of the earthly and mid-20 th century, namely, high emissions of particulate and gaseous pollutants from coal consumption for heating and industry, and frequent stagnation conditions due to subsidence inversions that impede pollutant dilution and transport (Hu et al, 2013; Shi et al, 2003; Zhao et al, 2009).…”
Section: Resultssupporting
confidence: 68%
“…Here, we applied generalized additive models (GAMs) (Hastie and Tibshirani 1990) to adjust for the nonlinear relationship between O 3 and NO x . GAMs have been applied extensively for both meteorological and nonmeteorological adjustment in air pollution trend analyses (Barmpadimos et al 2012; Zheng et al 2007; Jhun et al 2013). Trends of O 3 , NO x -adjusted O 3 , and NO x were calculated for each region, season, and time of day from the following GAMs, using the statistical package R (http://www.r-project.org): false(O3false)ij=β0+β1,actualyearij+γ0.16667emmonthij+δ0.16667emweekdayij+εij false(O3false)ij=β0+β1,adjustedyearij+γ0.16667emmonthij+δ0.16667emweekdayij+s((NOnormalx)ij)+εij false(NOxfalse)ij=β0+β1,NOxyearij+γ0.16667emmonthij+δ0.16667emweekdayij+εij where, (O 3 ) ij and (NO x ) ij represent O 3 and NO x concentrations, respectively, at site i and on date j and; β 1,actual , β 1,adjusted , and β 1,NOx estimate regional trends of O 3 , NO x -adjusted O 3 , and NO x , respectively, for a given season and hour of the day.…”
Section: Methodsmentioning
confidence: 99%
“…This finding may reflect that larger and heavier vehicular traffic is associated with lower sulfur content in diesel fuel (from S-500 to S-50 during 2012 and S-10 during 2013). In Santiago (Chile), Jhun et al 19 observed a 32% decrease in particulate sulfate as a consequence of the diesel sulfur reduction from 1500 to 50 mg kg -1 . Comparing the results obtained by Andrade et al 18 and the current work for the same sampling region (Duque de Caxias), several parameters differed by a factor of two.…”
Section: Resultsmentioning
confidence: 99%